Can difficult intubation be easily and rapidly predicted? - Fritscherova, Sarka; Adamus, Milan; Dostalova, Katerina; Koutna, Jirina; Hrabalek, Lumir; Zapletalova, Jana; Uvizl, Radovan; Janout, Vladimir (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2011)
AIM: Failed endotracheal intubation and inadequate ventilation with subsequent insufficient oxygenation can result in serious complications potentially leading to permanent health damage. Difficult intubation may occur not only in patients with apparent pathologies in the orofacial region but also, unexpectedly, in those without abnormalities. This study aimed at finding anthropometric parameters that are easy to examine and that would aid in predicting difficult intubation. METHOD: A case-control study was undertaken. Based on defined criteria, 15 parameters were examined in patients with unanticipated difficult intubation. The parameters included a previous history of difficult intubation, pathologies associated with difficult intubation, clinical symptoms of airway pathology, the Mallampati score, upper lip bite test, receding mandible, and cervical spine and temporomandibular joint movement. Thyromental, hyomental and sternomental distances and inter-incisor gap were measured. The methods were precisely defined and the measurements were carried out by a trained anesthesiologist. Statistical analysis was performed on data from 74 patients with difficult intubation and 74 control patients with easy intubation. RESULTS: Significant predictors of difficult intubation were inter-incisor gap (IIG), thyromental distance (TMD) and class 3 limited movement of the temporomandibular joint. The IIG and TMD cut-offs were set at 42 mm and 93 mm, respectively. CONCLUSION: The results will be used to confirm these predictors in an anesthesiology clinic along with the aid of the laryngoscopic findings to improve the prediction of unanticipated difficult intubation.
Keywords: laryngoskopie; Middle Aged; mužské pohlaví; ženské pohlaví; studie případů a kontrol; Intubation, Intratracheal; Humans; Airway Obstruction; zajištění dýchacích cest; Laryngoscopy; obstrukce dýchacích cest; intratracheální intubace; Airway Management; Female; Male; lidé; Case-Control Studies; lidé středního věku